KOPERASI SEBAGAI ALAT PEMBANGUNAN EKONOMI LOKAL: KAJIAN 5 KOPERASI DI AMERIKA, AUSTRALIA DAN EROPA - Stephanus Eri Kusuma (Department of Management - Institut Shanti Bhuana, 2022)
This study aims to describe the best practices in organizing a number of cooperatives that contribute to local economic development and identify te role of cooperatives in local economic development. This study is descriptive qualitative research using content analysis. The data source for this research is a video documentary on five cooperative organizations produced by the International Cooperative Alliance and the European Union Partnership on Cooperatives in the aroundtheworld.coop project. The result of this study indicates that cooperatives are able to play a role in local economic development by increasing the welfare of their members which is manifested in line with the ability of cooperatives in facilitating: (1) creation of access to employment and income, (2) provision of an environment that encourages capacity building and skills creation, (3) availability of access to economic resources, (4) creation of added value to production, (5) fulfillment of local community needs, (6) creation of supply chains for local producers, (7) mobilization of collective action to support equality of marginalized groups, (8) creation of opportunities to be involved in the management of organizations based on participation, (9) growth of social capital and social awareness, (10) creation of means of healing from social trauma, and (11) preservation of local culture.